Five Parts Dead - Pegler, Tim; Text Publishing ([Melbourne] : Text Publishing, 2010)
"What do you do when you've just lost three of your best mates? Who do you turn to when your life is suddenly bound to a wheelchair? Dan's still grieving when he's dragged on a family holiday to a remote island lighthouse. Left alone Dan starts sensing a mysterious girl. Is she a dream? Or has he somehow hooked into the spirit world?" -- Publisher.
For secondary school age readers.
Keywords: Friendship in adolescence -- Juvenile fiction; People with disabilities -- Fiction; Young adult fiction; Juvenile Fiction - General; Juvenile Fiction - Social Situations - Adolescence; Juvenile Fiction - Social Situations - Drugs, Alcohol, Substance Abuse; Australian; Road fiction